Evaluation Model: A New Approach to Assessing the Quality of Holistic Integrative Early Childhood Development Programs - Aip Saripudin; Herman Beni; Diani Magasida (Journal of General Education and Humanities, 2026)
The Holistic-Integrative Early Childhood Education (HI-ECD) program encompasses education, caregiving, health, protection, and child well-being; however, to date, no comprehensive, standardized evaluation model exists to assess the program's implementation in its entirety. This study aims to develop an evaluation model for the HI-ECD program that provides comprehensive information to improve the quality of basic services for young children. The study employed a Research and Development (R&D) approach by adapting the CIPP evaluation model to meet the specific needs of early childhood education units. The development process consisted of several stages, including a preliminary study, an initial design, expert validation, and product revision. The results indicate that the evaluation model developed—namely the IP-HIECD Evaluation Model—consists of two main components: input evaluation and process evaluation, complete with evaluation procedures, a user guide, and assessment instruments. Based on assessments from experts and practitioners, this model achieved a very good validity rating. These findings have implications for improving the effectiveness of HI-ECD program evaluation, providing a measurable overview of program achievements, and strengthening synergy among stakeholders in the management of HI-ECD services in Indonesia, ultimately contributing to the optimization of the growth and development of young children.